The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1371/journal.pone.0267284
|View full text |Cite
|
Sign up to set email alerts
|

“If it is not made easy for me, I will just not bother”. A qualitative exploration of the barriers and facilitators to recycling plastics

Abstract: Despite significant investment to increase recycling facilities and kerbside collection of waste materials, plastic packaging is frequently discarded as litter, resulting in significant environmental harm. This research uses qualitative methods to explore the contextual and psychological factors that influence plastic waste disposal behaviour from the perspectives of consumers. This research also reports key results from a brief online survey exploring consumer perspectives toward plastics and plastic recyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Psychology as a field clearly favors individual-level solutions. There are over 17,000 articles in Google Scholar from the past 20 years that mention increasing individual recycling, many of which point to structural barriers that obscure how people are supposed to recycle (De Young, 1990;Roy, Berry, & Dempster, 2022). We can, however, employ psychology and its individual-level tactics to force institutions and corporations to make hard choices, for good.…”
Section: It's Always Both: Changing Individuals Requires Changing Sys...mentioning
confidence: 99%
“…Psychology as a field clearly favors individual-level solutions. There are over 17,000 articles in Google Scholar from the past 20 years that mention increasing individual recycling, many of which point to structural barriers that obscure how people are supposed to recycle (De Young, 1990;Roy, Berry, & Dempster, 2022). We can, however, employ psychology and its individual-level tactics to force institutions and corporations to make hard choices, for good.…”
Section: It's Always Both: Changing Individuals Requires Changing Sys...mentioning
confidence: 99%
“…Health practitioners often stress the importance of simplicity and making the recommended actions easy to perform when promoting health behaviors (e.g., Koelen & Lindström, 2005; Michie et al, 2011). The plans we gave to half the participants provided more simplification of these participants’ actions, for example, by giving them access to relevant guidance at the time of action (Roy et al, 2022). Indeed, we observed that average exercise video use was at least three times higher in the plan than the no-plan condition—a finding that supports existing evidence for the effectiveness of action planning (Barz et al, 2016; Gollwitzer, 1999; Kwasnicka et al, 2013; Luszczynska et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Consumers consider the environment generally, but this kind of consideration will not turn into action one hundred percent [9]. They are hesitant at three factors: the first is that they are not sure which kind of plastics should be recycled, the second is that the recycling action is not so important in their daily life, and the third is that they think government can take this responsibility more easily than individuals.…”
Section: Literature Reviewmentioning
confidence: 99%